Os impactos do Decreto 11.150/2022 no tratamento do superendividamento no Brasil - Paula, Ana Gabriela Teixeira (2023)
This paper analyzes the unconstitutionality and illegality of Decree 11,150/2022, which defines a consumer’s existential minimum as twenty-five percent of the minimum wage in effect on the date of decree’s publication. The study begins by examining the possible causes for the population's over-indebtedness, and then analyzing the Non-compliance arguments relating to sections 1.005 and 1.006, and their impact of Decree 11.150/2022 on the treatment of over-indebtedness proposed by Law 14.181/2021. The method used in this article was deductive qualitative research, through the examination of the Brazilian legal apparatus on consumer rights, verifying the need for revocation of the Decree analyzed.